Social and Biological Parameters Involved in Suicide Ideation During the COVID-19 Pandemic: A Narrative Review. (December 2020) - Dhrisya, Chenthamara; Prasathkumar, Murugan; Becky, Robert; Anisha, Salim; Sadhasivam, Subramaniam; Essa, Musthafa Mohamed; Chidambaram, Saravana Babu; Al-Balushi, Buthainah; Guillemin, Gilles J; Qoronfleh, M Walid
Fear is an indispensable characteristic of any infectious disease, and the alarm will be further amplified when the infection spreads uncontrollable, unpredictable, and global. The novel corona virus (SARS CoV-2) lead Covid-19, has been declared as a global emergency by WHO as it has affected millions of people with a high mortality rate. The non-availability of medicine for Covid-19 and the various control measures such as social distancing, self-isolation, house quarantine, and the new normal implementation by different nations across the world to control the spread of Covid-19 made people vulnerable to fear and anxiety. As a result, considerable number of Covid-19-related suicidal deaths has been reported across the world during this pandemic. There have been several studies which describe the psychosocial aspects of suicidal ideation. However, the research on the biological aspects of suicidal ideation/suicidal risk factors that are related to pandemic are unreported. Hence this review article is intended to provide a comprehensive analysis of suicidal deaths during Covid-19 and also aimed to addresses the possible link between suicidal ideation and different factors, including psycho-social, behavioral, neurobiological factors (proximal, distal, and inflammatory) and immunity. The alterations in glutamatergic and GABAergic neurotransmitters had upregulated the GABARB3, GABARA4, GABARA3, GABARR1, GABARG2, and GAD2 gene expressions in suicidal victims. The changes in the Kynurenine (KYN) pathway, Hypothalamus-Pituitary-Adrenal axis (HPA axis) hyperactivation, and dysregulation of serotonin biosynthesis would significantly alter the brain chemistry in people with suicide ideation.